HUBUNGAN PENGGUNAAN GADGET DENGAN KEMANDIRIAN DALAM AKTIVITAS KESEHARIAN PADA ANAK USIA PRASEKOLAH - Nurlis; Sri Andala; Martunis (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2022)
One of the technologies favored by preschoolers today is gadgets. The negative impact of using gadgets is the children become more passive because children's focus shifts to gadgets so that it can affect children's independence in daily activities. The research objective was to determine the relationship between gadget use and independence in daily activities for preschooler in Gampong Riseh Tunong, Sawang District, Aceh Utara Regency. This research method used an analytical design with a cross sectional approach. The population used in this research was parents who had 50 children of preschool age in Gampong Riseh Tunong, Sawang District, Aceh Utara Regency. The samples were 50 people taken through total sampling technique and the instrument used a questionnaire and the data analysis used univariate and bivariate analysis. The results of this research showed that there was a relationship between the use of gadgets and independence in daily activities for preschooler in Gampong Riseh Tunong, Sawang District, Aceh Utara Regency, it was obtained P-value of 0.000 <α = 0.05. Based on the result above, it is expected the respondents can be wiser in supervising children, especially in providing restrictions and being selective in granting permission to use gadgets, distracting children by doing interesting things such as inviting children to play outside the house, inviting children to do more activities (sports, playing music) and socializing with their peers.